Alternative metrics for assessing clinical benefit with immunotherapy in oncology - Chan, E.; Hillengaß, Jens (OncoImmunology, 2018)
Therapies for cancer have traditionally been assessed with metrics such as the response rate, hazard ratio, or median survival. Such metrics have value in measuring the outcomes of conventional therapies, but may not be the most appropriate for new therapies. Immuno-oncology therapies offer a new approach to treating cancer by stimulating patients' immune systems to fight cancer. The value of these novel therapies has so far been assessed with traditional metrics, but the different ways in which immuno-oncology therapies work can mean the full value is not captured. Immuno-oncology therapies can produce longer survival times but this effect can be delayed or even preceded by an apparent phase of progression, which median survival or response rates may not reflect. This paper discusses a range of traditional and alternative metrics and their benefits or disadvantages in measuring the effects of immuno-oncology therapies, using examples of several novel drugs as case studies.